1974
DOI: 10.1073/pnas.71.4.1133
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Replacement of Methionine by Homocystine on Survival of Malignant and Normal Adult Mammalian Cells in Culture

Abstract: In tissue cultures of normal adult and malignant mammalian cells, homocystine has been substituted for methionine in a medium rich in folic acid and cyanocobalamin. Normal adult cells thrive. Three highly malignant cell types from three different species, including man, die.A metabolic defect seen to date only in cancer cells was uncovered during an investigation of transfer RNA methylation using tissue cultures of normal adult and malignant cells (1,2). In several lines of malignant cells we have observed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
1
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 17 publications
6
103
1
1
Order By: Relevance
“…It has been suggested that growth arrest by methionine restriction may be related to the role of methionine as a methyl donor for methylation of DNA, RNA and proteins (Lu and Epner, 2000). Interestingly, normal cells are able to grow in culture when methionine is substituted with homocysteine because mammalian cells can convert homocysteine to methionine (Stern and Hoffman, 1986), but most cancer cells fail to grow in the absence of methionine, even when supplemented with homocysteine (Halpern et al, 1974;Mecham et al, 1983;Stern and Hoffman, 1986), which may result from the elevated levels of transmethylation in cancer cells as compared with normal cells (Tisdale, 1980;Stern and Hoffman, 1984;Judde et al, 1989). It was recently reported that telomeric recombination was elevated by a decrease in methylation of sub-telomeric regions in mouse embryonic stem (ES) cells deficient for DNA Figure 5 Correlation among TRF1, TRF2, TIN2 and RAP1 foci in IIICF/c cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that growth arrest by methionine restriction may be related to the role of methionine as a methyl donor for methylation of DNA, RNA and proteins (Lu and Epner, 2000). Interestingly, normal cells are able to grow in culture when methionine is substituted with homocysteine because mammalian cells can convert homocysteine to methionine (Stern and Hoffman, 1986), but most cancer cells fail to grow in the absence of methionine, even when supplemented with homocysteine (Halpern et al, 1974;Mecham et al, 1983;Stern and Hoffman, 1986), which may result from the elevated levels of transmethylation in cancer cells as compared with normal cells (Tisdale, 1980;Stern and Hoffman, 1984;Judde et al, 1989). It was recently reported that telomeric recombination was elevated by a decrease in methylation of sub-telomeric regions in mouse embryonic stem (ES) cells deficient for DNA Figure 5 Correlation among TRF1, TRF2, TIN2 and RAP1 foci in IIICF/c cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, availability of homocysteine does not rescue cancer cells from their methionine dependence. [5][6][7][8] Importantly, remethylation of homocysteine to generate methionine appears to be unaffected in cancer cells. 9 Cancer cell methionine dependency is well-documented.…”
Section: Introductionmentioning
confidence: 99%
“…When the same cells are cultured in methionine stress conditions, methionine-free media supplemented with homocysteine (Met-Hcy+), after 1 wk only normal cells exist in the culture dish. 6 In vitro studies of prostate cancer cells indicate that they suffer a specific cell cycle arrest and eventually undergo apoptosis when cultured in Met-Hcy+ media. 10 Consistent with a specific effect of methionine restriction non-transformed cells but leads to cell proliferation block in many cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Walker 256 carcinosarcoma in cell culture shows methionine auxotrophy (Halpern et al, 1974) which cannot be explained by the lack of methionine synthetase (Hoffman & Erbe, 1976). In these experiments no 5-CH3THF derivatives were found in Walker 256 carcinosarcoma extracts except shortly after administration of FA.…”
Section: Discussionmentioning
confidence: 99%